Global environmental change - Charles, Rosemary (Callisto Reference, 2015)
Environmental transformation is increasingly considered a crucial subject for scientists across various disciplines, as well as policy makers around the globe. Mounting evidence reveals that environments around the globe are undergoing some drastic changes. Increasing population, urbanization and development of the global economy are putting more pressure on ecosystems. To comprehend the roots and consequences of environmental modification, the writers of this book employ spatial and non-spatial data, different theoretical visions, and cutting edge research tools such as GIS, remote sensing technology, etc. Global perspectives on environmental modification bring together research around the world to investigate the complexities of modern and historical environmental change. Features of environmental modification explored in this book include: climate change, historical environmental change and biological responses to environmental change.